2003
DOI: 10.1074/jbc.m304437200
|View full text |Cite
|
Sign up to set email alerts
|

20-Hydroxyeicosatetraenoic Acid (20-HETE) Activates Mouse TRPC6 Channels Expressed in HEK293 Cells

Abstract: In the present study, we show that the eicosanoid compound, 20-hydroxyeicosatetraenoic acid (20-HETE), an important arachidonic acid metabolite, activates mouse TRPC6 in a stable, overexpressing HEK293 cell line, Hek-t6.11. Application of 20-HETE rapidly induced an inward, non-selective current in whole-cell recordings, which was inhibited by N-methyl-D-glucamine, 1.8 mM Ca 2؉ , and 100 M Gd 3؉ but remained unaffected by flufenamate and indomethacin. The current-voltage relationship obtained at low concentrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
62
2

Year Published

2004
2004
2019
2019

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 94 publications
(65 citation statements)
references
References 47 publications
1
62
2
Order By: Relevance
“…This result contrasts with the data recently reported to explain the inotropic effects and mode of action of 20-HETE on ASM cells, which are known to express various lipid-gated nonselective cationic TRPC channel isoforms (2,6,31). Among those, TRPC3 and -6 are recognized as direct modulators of resting smooth muscle tone (1,2,6). In contrast to Gd 3ϩ , nifedipine relaxes 48.1% the tension induced by 5-oxo-ETE, suggesting that L-type Ca 2ϩ channels (14) are directly involved in the control of ASM tone triggered by this eicosanoid.…”
Section: Discussioncontrasting
confidence: 55%
See 1 more Smart Citation
“…This result contrasts with the data recently reported to explain the inotropic effects and mode of action of 20-HETE on ASM cells, which are known to express various lipid-gated nonselective cationic TRPC channel isoforms (2,6,31). Among those, TRPC3 and -6 are recognized as direct modulators of resting smooth muscle tone (1,2,6). In contrast to Gd 3ϩ , nifedipine relaxes 48.1% the tension induced by 5-oxo-ETE, suggesting that L-type Ca 2ϩ channels (14) are directly involved in the control of ASM tone triggered by this eicosanoid.…”
Section: Discussioncontrasting
confidence: 55%
“…In bronchi, Ca 2ϩ entry could also result from the activation of the capacitative Ca 2ϩ entry after depletion of intracellular Ca 2ϩ stores, as reported previously (6). Nevertheless, the tonic response induced by 5-oxo-ETE was poorly sensitive to 100 M Gd 3ϩ , a concentration known to block both capacitative and noncapacitative Ca 2ϩ entry (1,4,6), suggesting that this process contributes only marginally to the response to 5-oxo-ETE. This result contrasts with the data recently reported to explain the inotropic effects and mode of action of 20-HETE on ASM cells, which are known to express various lipid-gated nonselective cationic TRPC channel isoforms (2,6,31).…”
Section: Discussionmentioning
confidence: 73%
“…These channels appear to belong to the TRPC3/6 subtypes, highly expressed in CB glomus cells (30) and having a pharmacology compatible with that observed for the background Na ϩ current (33,34). Heterologously expressed recombinant TRPC6 channels exhibit single-channel events quite similar to those observed in glomus cells after activation by low glucose or 1-oleoyl-2-acetyl-snglycerol (39). Interestingly, TRPC3 channels have been shown to be directly involved in Ca 2ϩ signaling, since Na ϩ influx is coupled with reversal activation of the Na ϩ /Ca 2ϩ exchanger, thus leading to the rise of cytosolic Ca 2ϩ (40).…”
Section: Discussionmentioning
confidence: 74%
“…TRPC6 was the first ion channel identified that is activated by DAG in a membrane-delimited fashion, independently of protein kinases C. The exact location of a putative binding site for diacylglycerols in the TRPC6 protein is still elusive because an OAG-insensitive splice variant of TRPC6, (TRPC6B; Zhang and Saffen 2001) characterized by means of fluorometry turned out to be activated by DAG when analyzed by electrophysiological methods (Jung et al 2003). More recently, TRPC6 has also been reported to be sensitive to the arachidonic acid metabolite 20-hydroxyeicosatetraenoic acid (Basora et al 2003). In contrast to the scenario with TRPC6 which is a tightly receptor-regulated store-independent cation channel, TRPC3 and TRPC7 display considerable basal activity (see Fig.…”
Section: Trpc6mentioning
confidence: 89%